Cultural Heritage as a Legal Hybrid Between Public and Private Law - Jagielska-Burduk, Alicja (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book examines cultural heritage law in both its public and private modalities, focusing on the search for new solutions in national legislations. Both tangible and intangible cultural heritage pose challenges for national legislation regarding the legal histories of the respective countries, obligations deriving from international law, and the independence of respective national searches for a tailored protection model. Although the concept of cultural heritage transcends civil law regulation and property rights, it must be considered when attempting to establish any coherent cultural heritage protection system. In national legislation, we can now observe an increased interest in leveraging civil law or private law to strengthen cultural heritage protection systems. This book looks beyond public and private law on cultural heritage in order to address its complex status as a legal hybrid. Further, the book shows how current problems in the international debate are mirrored in national legislation. Poland is used as a practical example, while also referring to other countries' solutions as well as EU and international law instruments. This approach enables the reader to examine the creation of national legislation at the operational level and provides a template for all national lawyers concerning current challenges and emerging trends. The book's target audience includes researchers and practitioners in the field of cultural heritage law, as well as public and private law experts. The topics covered can also be helpful for law students, art market actors, and all those interested in the challenges of cultural heritage protection.
Cultural heritage as a legal hybrid. Between public and private law -- Cultural heritage. Legal concepts and protection Cultural heritage forms. Legal challenges -- Polish private law and cultural heritage -- A new approach to cultural heritage and the legal regime of common resources in Poland -- Cultural heritage protection in private law. In search of new solutions.
Keywords: Private international law; Conflict of laws; International law; Comparative law; Law-Europe.; Human rights; Cultural property; Archaeology; Private International Law, International and Foreign Law, Comparative Law; Public International Law; European Law; Human Rights; Cultural Heritage; Heritage Management